The Magistrates of the Roman Republic, by T. Robert S. Broughton et al. | The Online Books Page
Keywords: _open access

Prosopographia Imperii Romani (PIR)
Keywords: _open access

itiner-e - The Digital Atlas of Ancient Roads
Itiner-e aims to host the most detailed open digital dataset of roads in the entire Roman Empire. The data creation is a collaborative ongoing project edited by a scholarly community. Itiner-e allows you to view, query and download roads.
Keywords: _open access

Projets Time Machine. Construire et diffuser ensemble des référentiels géohistoriques (Projets Time Machine)
Keywords: _open access

Royal Ontario Museum
Collections consacrées à l’art, à la nature et aux cultures du monde entier et de toutes les époques
Keywords: _open access

British History Online
The core printed primary and secondary sources for the medieval and modern history of the British Isles
Keywords: _open access

World Historical Gazetteer
Index of place records with coordinates, historical metadata, linked toponyms, and ecological classifications
Keywords: _open access

Project Gutenberg (Project Gutenberg)
Project Gutenberg is a library of free eBooks.
Keywords: _open access

Gallica
Keywords: _open access